2021
DOI: 10.1109/tuffc.2021.3078094
|View full text |Cite
|
Sign up to set email alerts
|

Histotripsy Ablation Alters the Tumor Microenvironment and Promotes Immune System Activation in a Subcutaneous Model of Pancreatic Cancer

Abstract: Pancreatic cancer is a significant cause of cancerrelated deaths in the United States with an abysmal 5-year overall survival rate that is under 9%. Reasons for this mortality include the lack of late-stage treatment options and the immunosuppressive tumor microenvironment. Histotripsy is an ultrasound-guided, non-invasive, non-thermal tumor ablation therapy that mechanically lyses targeted cells. To study the effects of histotripsy on pancreatic cancer, we utilized an in vitro model of pancreatic adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 64 publications
(96 reference statements)
4
31
0
Order By: Relevance
“…In mouse models, histotripsy ablation of hepatic, renal, neuroblastoma, melanoma, and pancreatic tumors has resulted in significantly increased survival (22,(110)(111)(112)(113). In addition to debulking tumors, recent evidence has suggested that histotripsy has the capability to induce a systemic immune response, as evidenced by the attenuation of metastasis and an improvement in local and distant disease with combination immunotherapy (22,114,115).…”
Section: Histotripsy: Non-thermal Non-invasive Tumor Ablationmentioning
confidence: 99%
“…In mouse models, histotripsy ablation of hepatic, renal, neuroblastoma, melanoma, and pancreatic tumors has resulted in significantly increased survival (22,(110)(111)(112)(113). In addition to debulking tumors, recent evidence has suggested that histotripsy has the capability to induce a systemic immune response, as evidenced by the attenuation of metastasis and an improvement in local and distant disease with combination immunotherapy (22,114,115).…”
Section: Histotripsy: Non-thermal Non-invasive Tumor Ablationmentioning
confidence: 99%
“…No changes in immune cells in the microenvironment of the tumours were seen 24 h and 7 days after histotripsy, and then a decrease in macrophages (percentage of CD45 + cells) and regulatory T cells (percentage of total cells) and an increase in DC (as a percentage of CD45 + cells) was seen 14 days after histotripsy treatments. The same authors also showed the release of DAMPS, including HMGB1 release, after the treatment of the Pan02 cells in vitro with the same histotripsy parameters (parameters: f = 1 MHz, 8 elements, f-number = 0.68, focus = 0.98 × 0.93 × 3.9 mm, pulses < 2 cycles, prf = 250 Hz) [204]. Sonodynamic therapy has also shown pro-immune effects in preclinical models of pancreatic cancer.…”
Section: The Immunological Effects Of Therapeutic Focused Ultrasound ...mentioning
confidence: 89%
“…More anecdotally, two case studies reported abscopal effects following thermal ablation [ 111 , 112 ]. Preclinical data regarding immune effects in animal models of pancreatic cancer have recently been published [ 100 , 101 , 113 , 114 ]. The interested reader can refer to the detailed comprehensive review of those studies recently provided by Mouratidis and ter Haar [ 115 ].…”
Section: Immunotherapymentioning
confidence: 99%